Distribution of the burrows of Bufo fernandezae (Anura, Bufonidae) outside of the breeding season - Rosset, Sergio Daniel; Alcalde, Leandro (Phyllomedusa: Journal of Herpetology, 2004)
We studied the spatial distribution of a population of adult Bufo fernandezae based on the spatial arrangement of their burrows. The study was carried out in a suburban area near La Plata, Argentina. Two sampling methods were used: counts of burrows on areas of known size (quadrat sampling) and distance measures (plotless sampling). Data obtained using both methods indicate that the spatial distribution in the analyzed population is at random. In agreement with one of the assumptions of random distributions, burrow density was not significantly correlated with distance to water bodies, soil hardness and vegetation cover at the studied spatial scale. Respect to the other assumption of random distributions, we did not obtain data to assess it independently. Positive interactions such as aggregations to avoid water loss described for others species of Bufo do not occur in B. fernandezae because toads of this species solve this problem living in individual burrows. Negative interactions such as territoriality were not evident herein probably because at the population density found (1 individual by 83 m²) competition by resources decreases. We emphasize the utility of the methods used here to apply in future works that need to obtain data about the response of B. fernandezae's populations exposed to different environmental conditions.